Gambaran tingkat pengetahuan remaja putri usia 10-19 tahun tentang personal hygiene saat menstruasi - Pangesti, Dimas Ning; Milindasari, Praty (JOURNAL OF Tropical Medicine Issues, 2024)
Background: Knowledge is the result of knowing and this occurs after people have sensed a certain object. Menstruation is a natural process that occurs in women. Menstruation is regular bleeding from the uterus as a sign that the uterine organs have matured. Personal hygiene is an action taken to maintain the cleanliness and health of a person for physical and psychological well-being. Purpose: To identifying the level of knowledge of adolescent girls aged 10-19 years about personal hygiene during menstruation. Method: A descriptive. The respondents used in this study were 30 respondents. The sampling used was accidental sampling. Results: Conducted on 30 respondents showed the level of knowledge of adolescents aged 10-19 years about personal hygiene in RT 15, the results showed that the level of knowledge was good in adolescents as many as 12 (40%) respondents, the level of knowledge was sufficient as many as 15 (50%) respondents, and the level of knowledge was sufficient for 15 (50%) respondents. lack of knowledge as many as 3 (10%) respondents. The average level of good knowledge in adolescents is 12 (40%) namely from high school education, sufficient knowledge level is 15 (50%), namely high school education 3 respondents, junior high school 7 respondents and elementary school 5 respondents. The level of knowledge is less than 3 (10%) elementary education. Conclusion: Based on the age of 10-19 years, the average number of respondents aged 14-19 years was 22 (73%). The average education of the respondents is SMA 15%. The average occupation of the respondent's parents is 15 (50%) self-employed. Keyword: Adolescents; Knowledge Level; Menstruation; Personal Hygiene. Pendahuluan: Pengetahuan merupakan hasil tahu dan ini terjadi setelah orang melakukan penginderaan terhadap suatu objek tertentu. Menstruasi adalah proses alamiah yang terjadi pada perempuan. Menstruasi merupakan perdarahan teratur dari uterus sebagai tanda bahwa organ kandungan telah berfungsi matang. Kebersihan perorangan adalah suatu tindakan yang dilakukan untuk memelihara kebersihan dan kesehatan seseorang untuk kesejahteraan fisik dan psikis. Tujuan: Untuk mengidentifikasi tingkat pengetahuan remaja putri usia 10-19 tahun tentang personal hygiene saat menstruasi. Metode: Deskriptif. Responden yang digunakan pada peneitian ini sebanyak 30 responden. Sampling yang digunakan yaitu accidentalsampling,. Hasil: Pada 30 responden menunjukkan tingkat pengetahuan remaja usia 10-19 tahun tentang personal hygiene di RT 15 didapatkan hasil tingkat pengetahuan baik pada remaja sebanyak 12 (40% ) responden, tingkat pengetahuan cukup sebanyak 15 (50%) responden, dan tingkat pengetahuan kurang sebanyak 3 (10%) responden. Rata-rata tingkat pengetahuan baik pada remaja sebanyak 12 (40% ) yaitu dari pendidikan SMA, tingkat pengetahuan cukup sebanyak 15 (50%) yaitu pendidikan SMA 3 responden, SMP sejumlah 7 responden dan SD sejumlah 5 responden. Tingkat pengetahuan kurang sejumlah 3 (10%) pendidikan SD. Simpulan: Karakteristik responden berdasarkan usia 10-19 tahun, rata-rata responden yaitu berusia 14-19 tahun sejumlah 22 (73%). Rata-rata pendidikan responden yaitu SMA 15%. Rata-rata pekerjaan orang tua responden yaitu wiraswasta sejumah 15 (50%). Kata Kunci: Menstruasi; Personal Hygiene; Remaja; Tingkat Pengetahuan.